Extra Storage Capacity Enabled by Structural Defects in Pseudocapacitive NbN Monocrystals for High‐Energy Hybrid Supercapacitors. (27th February 2022) - Zhou, Shaowen; Chiang, Chao‐Lung; Zhao, Jianqing; Cheng, Guanjian; Bashir, Tariq; Yin, Wanjian; Yao, Junyi; Yang, Shiqi; Li, Wanying; Wang, Jiaqi; Wang, Xinyuan; Lin, Yan‐Gu; et al.
Abstract: Li‐ion hybrid supercapacitors (LHSCs) are intensely studied due to their favorable power densities. However, combined higher energy density materials, particularly anodes, are desirably sought. Herein, a defect‐dominating structure protocol is reported. Specifically, two visible structural defects, i.e., crystal vacancy and lattice distortion have been introduced in situ in ultrafine niobium nitride (NbN) monocrystals that are integrated into a carbon (C) framework. Highly reversible Li‐ion storage capacities up to 540 mAh g −1 are demonstrated in such a NbN@C composite anode, together with excellent rate capability and cycling stability. An extra vacancy‐induced capacity contribution of the defective NbN component is evidenced by first‐principles density functional theory (DFT) simulations in contrast to perfect modeling. Coupling with an activated carbon (AC) cathode, the NbN@C//AC cell can deliver balanced energy and power densities of 53.8 Wh kg −1 and 7818 W kg −1 at 4 A g −1, and retain a desired energy density of 56.1 Wh kg −1 after 10 000 cycles at 1 A g −1 . Findings from this study, particularly the demonstrated defects‐induced extra capacity of pseudocapacitive materials, may inspire new structural material designs of LHSCs. Abstract : Lattice flaws and nano‐engineering are excellent strategies for increasing the favourable space for lithium ion insertion and extraction in electrode materials. This study incorporates defects and vacancies into the pseudocapacitance material NbN, resulting in an ultra‐small nanoparticle carbon composite with exceptional electrochemical performance.